Shanghai Time Outside to Reduce Myopia trial: design and baseline data - He, Xiangui; Sankaridurg, Padmaja; Xiong, Shuyu; Li, Wayne; Zhang, Bo; Weng, Rebecca; Zhu, Jianfeng; Naduvilath, Thomas; Resnikoff, Serge; Zou, Haidong; Xu, Xun (Clinical & experimental ophthalmology, 2019)
Importance Myopia is a major public health concern worldwide, while outdoor time is indicated to be protective against the onset of myopia. Background To describe the methodology and baseline data of the Shanghai Time Outside to Reduce Myopia (STORM) trial. Design A 2‐year, school‐based, prospective, cluster randomized trial. Participants Children from grade I and II classes of 24 schools from eight districts in Shanghai, China, were randomized to either a control group, a test group I (40‐min outdoor time/day) or test group II (80‐min outdoor time/day). Methods At baseline and annual intervals, cycloplegic autorefraction and axial length measurement will be performed. Time outdoors and light exposure will be monitored via parent/carer questionnaires and a wearable device. Main Outcome Measures Spherical equivalent, prevalence of myopia and time outdoors in each group. Results A total of 6295 eligible children (age 7.2 ± 0.7 y [6‐9 y]) were randomized to control (n = 2037), test group I (n = 2329) and test group II (n = 1929). At baseline, spherical equivalent was +0.98 ± 1.02D, +1.02 ± 1.02D and +1.00 ± 0.99D (P = 0.708), myopia prevalence was 8.9, 7.7 and 7.8% (P = 0.270) and time outdoors was 58.5 ± 35.8, 59.8 ± 34.7 and 58.5 ± 35.3 min/d (P = 0.886) for control, test groups I and II, respectively. Conclusions and Relevance Myopia prevalence was high at nearly 8 to 9% in school children aged 7 years in Shanghai, China. The current trial will help evaluate if increased time outdoors has a role to play in reducing the incidence of myopia and/or slow the progression of myopia.